The microcomputer converter of the telex signal - Hottmar, Vladimir; Kuba, Michal (Communications - Scientific letters of the University of Zilina, 2004)
This paper deals with a structure and a description of the microcomputer converter of the telex signal (MCTS) that we developed for the Slovak Telecom. The microcomputer converter was developed within the International contract between Hungary Telecommunication Association Matav, Slovak Telecom in Bratislava, and Department of Telecommunications at the University of Zilina. We made the following tasks: design, debugging and testing of the resident program of the converter. After evaluation of the prototype by the company Matav 150 pieces of the converters, were manufactured and then successfully implemented in the TELEX exchange in Slovak Telecom in Bratislava for continuous operation.